ChatGPT sebagai Asisten Pengajar: Pemanfaatan Generative AI untuk Efisiensi Pembuatan Materi Ajar dan Soal Evaluasi - Abd. Rahman Saleh; Muhammad Naim; Muhammad Ikhwan Ahmad; Suherni Suherni; Sukriati Sukriati (FKIP UNSULTRA, 2025)
The development of generative artificial intelligence (AI) technology has brought significant changes to modern education. One prominent implementation is the use of ChatGPT as a teaching assistant capable of supporting the process of creating teaching materials and assessment questions more efficiently. This literature review aims to examine ChatGPT's potential in improving teacher effectiveness, particularly in the context of primary and secondary education. The study was conducted through a systematic review of various scientific publications published between 2022 and 2025 that discuss the application of generative AI in education. The analysis results indicate that ChatGPT can be used to generate learning material designs, automatically compile questions, and provide early feedback on student learning outcomes. The use of ChatGPT has been proven to save time in the learning design process, allowing teachers to focus more on pedagogical aspects and interactions with students. However, key challenges identified include the accuracy of the generated content, the potential for algorithmic bias, and issues of academic integrity, which require serious attention. Furthermore, clear institutional policies are needed, as well as improving digital literacy and ethical use of AI among educators. Based on the review results, it was concluded that ChatGPT has strategic potential as a teacher aid to support learning efficiency and innovation, as long as its use is directed wisely and accompanied by professional supervision to ensure it remains aligned with educational goals oriented toward character development and 21st-century competencies.